Long term deflection and cracking performance of palm shell aggregate concrete beam subjected to transverse loading - Liew, Yu Voon (Universiti Malaysia Sarawak (UNIMAS), 2010)
The research is about the use of oil palm shell (OPS) as coarse aggregate to produce structural concrete. An experimental investigation was designed to study the deflection and cracking behavior of Oil Palm Shell (OPS) beams and normal weight concrete beams under long-term sustained loading. Flexural test also involved in this study. Nine concrete beams were prepared at laboratory. Four OPS concrete beams and two normal weight concrete beams were subjected to different loading in four months. (120 days) The other two OPS concrete beams and one normal weight concrete beam were used to carry out the flexural test. From the experimental observation and theoretical analysis, the result shows that cracked section beams under sustained loading had produced larger deflection comparing to the uncracked section beams. This incident was concluded that theoretical approaches are able to give closer estimate of deflection for the larger values of creep function. In addition, OPS concrete beams showed larger deflection comparing to the normal weight concrete beam. The results from flexural test showed the loading that had applied to OPS concrete beam less than the loading that applied to the normal Weight concrete beams. Besides, the experimental results obtained were less than the theoretical result.